Deep Plane Facelifting for Facial Rejuvenation - Gordon, Neil; Adam, Stewart (Facial Plastic Surgery, 2014)
The purpose of this article is to provide the facial plastic surgeon with anatomical and embryologic evidence to support the use of the deep plane technique for optimal treatment of facial aging. A detailed description of the procedure is provided to allow safe and consistent performance. Insights into anatomical landmarks, technical nuances, and alternative approaches for facial variations are presented. The following points will be further elucidated in the article. The platysma muscle/submuscular aponeurotic system/galea are the continuous superficial cervical fascia encompassing the majority of facial fat, and this superficial soft tissue envelope is poorly anchored to the face. The deep cervical fascia binds the structural aspects of the face and covers the facial nerve and buccal fat pad. Facial aging is mainly due to gravity's long-term effects on the superficial soft tissue envelope, with more subtle effects on the deeper structural compartments. The deep plane is the embryologic cleavage plane between these fascial layers, and is the logical place for facial dissection. The deep plane allows access to the buccal fat pad for treatment of jowling. Soft tissue mobilization is maximized in deep plane dissections and requires careful hairline planning. Flap advancement creates tension only at the fascia level allowing natural, tension-free skin closure, and long-lasting outcomes. The deep plane advancement flap is well vascularized and resistant to complications.
Keywords: deep plane; facelift; rhytidectomy; aging face